Microstructural characterization of biofunctionalized titanium foams - Teixeira, M. (2015)
This study was supported by The Calouste Gulbenkian Foundation through “Programa de Mobilidade Académica para Professores”, “Ações Integradas Luso-Francesas 2014 - ref.ª: TC-12_14”, and the Portuguese Foundation for Science and Technology (FCT–Portugal), under the project EXCL/EMS-TEC/0460/2012.